Análisis financiero basado en la técnica de Fuzzy Logic para la estabilidad financiera en la cooperativa de ahorro y crédito Sumac Llacta Ltda. Período 2019-2022 - Cuji García, María Genoveva (2024)
ABSTRACT: The objective of this research was to analyze the financial statements using the fuzzy logic technique to determine the financial stability of the Cooperativa de Ahorro y Crédito Sumac Llacta Ltda., for the period 2019-2022. The study adopted a quantitative and descriptive perspective, using documentary sources and data collection in the field; the design used was not experimental. The applied approach was deductive; its population was the Cooperative of Savings and Credit Sumac Llacta and the techniques used were observation and analysis of documents with their respective instruments, the observation guide, and the document analysis guide. The results revealed that the equity adequacy ratios and Return on Average Assets (ROA) belong to the fuzzy sets in fuzzy logic trapezoidal conditions, concluding that the fuzzy logic technique confirms the concerns previously identified in the financial statements of Cooperativa de Ahorro y Crédito Sumac Llacta. It provides a complete picture of financial health, permitting decisions that will improve financial stability and benefit its members. Keywords: Fuzzy Logic, Linguistic Variables, Trapezoidal Function, Cooperatives, Financial Indicators, Decadal Scale.